Centenarian Exomes as a Tool for Evaluating the Clinical Relevance of Germline Tumor Suppressor Mutations. (31st March 2020) - Balabanski, Lubomir; Serbezov, Dimitar; Nikolova, Dragomira; Antonova, Olga; Nesheva, Desislava; Hammoudeh, Zora; Vazharova, Radoslava; Karachanak-Yankova, Sena; Staneva, Rada; Mihaylova, Marta; Damyanova, Vera; Hadjidekova, Savina; et al.
Objectives: The aim of the present study was to evaluate the clinical relevance of mutations in tumor suppressor genes using whole-exome sequencing data from centenarians and young healthy individuals. Methods: Two pools, one of centenarians and one of young individuals, were constructed and whole-exome sequencing was performed. We examined the whole-exome sequencing data of Bulgarian individuals for carriership of tumor suppressor gene variants. Results: Of all variants annotated in both pools, 5080 (0.06%) are variants in tumor suppressor genes but only 46 show significant difference in allele frequencies between the two studied groups. Four variants (0.004%) are pathogenic/risk factors according to single nucleotide polymorphism database: rs1566734 in PTPRJ, rs861539 in XRCC3, rs203462 in AKAP10, and rs486907 in RNASEL . Discussion: Based on their high minor allele frequencies and presence in the centenarian group, we could reclassify them from pathogenic/risk factors to benign. Our study shows that centenarian exomes can be used for re-evaluating the clinically uncertain variants.